Live yeast in juvenile diet induces species-specific effects on Drosophila adult behaviour and fitness - Murgier, Juliette (Sci Rep, 2019)
The presence and the amount of specific yeasts in the diet of saprophagous insects such as Drosophila can affect their development and fitness. However, the impact of different yeast species in the juvenile diet has rarely been investigated. Here, we measured the behavioural and fitness effects of three live yeasts (Saccharomyces cerevisiae = SC; Hanseniaspora uvarum = HU; Metschnikowia pulcherrima = MP) added to the diet of Drosophila melanogaster larvae. Beside these live yeast species naturally found in natural Drosophila populations or in their food sources, we tested the inactivated “drySC” yeast widely used in Drosophila research laboratories. All flies were transferred to drySC medium immediately after adult emergence, and several life traits and behaviours were measured. These four yeast diets had different effects on pre-imaginal development: HU-rich diet tended to shorten the “egg-to-pupa” period of development while MP-rich diet induced higher larval lethality compared to other diets. Pre- and postzygotic reproduction-related characters (copulatory ability, fecundity, cuticular pheromones) varied according to juvenile diet and sex. Juvenile diet also changed adult food choice preference and longevity. These results indicate that specific yeast species present in natural food sources and ingested by larvae can affect their adult characters crucial for fitness.